Migration into art : transcultural identities and art-making in a globalised world - Petersen, Anne Ring (Rethinking art's histories., 2017)
This book addresses a topic of increasing importance to artists, art historians and scholars of cultural studies, migration studies and international relations: migration as a profoundly transforming force that has remodelled artistic and art institutional practices across the world. It explores contemporary art's critical engagement with migration and globalisation as a key source for improving our understanding of how these processes transform identities, cultures, institutions and geopolitics. The author explores three interwoven issues of enduring interest: identity and belonging, institutional visibility and recognition of migrant artists, and the interrelations between aesthetics and politics, including the balancing of aesthetics, politics and ethics in representations of forced migration.